Weight reduction by topology optimization of an engine subframe mount, designed for additive manufacturing production - Merulla, Andrea; Gatto, Andrea; Bassoli, Elena; Munteanu, Sorin Ion; Gheorghiu, Bogdan; Pop, Mihai Alin; Bedo, Tibor; Munteanu, Daniel (Elsevier BV, 2019)
Additive Manufacturing (AM) technologies are getting more and more strategic for different purposes in many industrial fields. Among the most outstanding are part prototyping, single part to small batch production, relatively reduced manufacturing times and investments costs, reduced material consumption, and innovative and efficient shapes. The considerable advantages these technologies offer, compared to subtractive ones, make additive manufacturing a potentially industry-leading process in almost all domains - from aeronautics to the medical industry. Under these circumstances, the inspiration given by topology optimization tools can lead to feasible industrial parts, with fewer constraints in comparison to traditional manufacturing processes. The paper presents the development and the results obtained using topology optimization and design for AM technology on an automotive part: an engine mount sub-frame component for a rear middle engine sports car. The final design enables a significant weight reduction.
Keywords: additive manufacturing; topology optimisation; weight reduction